Effects of dispersant content and pH on dispersion of suspension, microstructures and electrical properties of ZnO varistors. Issue 9 (15th June 2020) - Ruan, Xuejun; Ren, Xin; Zhou, Wenting; Cheng, Qi; Yao, Zheng; Yu, Wenqi; Jin, Lujiang; Shi, Liyi
Abstract: This article systematically studies the relationship between the dispersity of the mixed suspension, the microstructures and the electrical properties of the ZnO varistors by adjusting the dispersant content and the pH value. The suspension dispersity was measured by viscosity, zeta potential, particle size distribution and TEM observation. The structure of the as-prepared ZnO varistors was characterized by XRD and SEM. The electrical properties were investigated by testing E-J characteristics, breakdown voltage, leakage current, nonlinear coefficient, 8/20 μs waveform current impulse and accelerated aging performance. When the suspension reached the best dispersion condition of 0.3 wt% dispersant and the original pH value, the ZnO varistors had optimum electrical properties: breakdown voltage gradient of 299.95 V mm −1, leakage current IL of 0.33 μA, voltage ratio U5kA /U1mA of 1.686, nonlinear coefficient of 46.71, and a downward trend of power consumption in the accelerated aging test.